2021
DOI: 10.1016/j.envres.2021.111293
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short- and long-term exposure to atmospheric pollution on COVID-19 risk and fatality: analysis of the first epidemic wave in northern Italy

Abstract: The effects of exposure to atmospheric pollution on the incidence and mortality due to COVID-19 have been studied but not for sulfur dioxide (SO 2 ) in most studies. However, most studies failed to consider important cofounding factors in the estimation of health effects of air pollution. The objective of the study was to assess the short- and long-term effects of air pollution on the COVID-19 risk and fatality in Lombardy and Veneto. Air pollutants were studied based on monitoring stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…It would be probably linked to an increased susceptibility of the host, which in turn, could be due to the dysregulation of the immune system, or also to the worsening of the conditions associated with severe SARS-CoV-2 infections. Recently, Ho et al (2021) have reported the results of an analysis performed in the Lombardy and Veneto regions, on the contribution of NO 2 , PM 2.5 , PM 10 , O 3 and SO 2 to the incidence, mortality, and fatality rates of COVID-19, both short- and long-term exposure for 8 years (January 2013–May 2020). The most striking result was the finding of the significant role of exposure to SO 2 in COVID-19 pandemic via inducing systemic and respiratory inflammation.…”
Section: Recent Studies By Continents and Countriesmentioning
confidence: 99%
“…It would be probably linked to an increased susceptibility of the host, which in turn, could be due to the dysregulation of the immune system, or also to the worsening of the conditions associated with severe SARS-CoV-2 infections. Recently, Ho et al (2021) have reported the results of an analysis performed in the Lombardy and Veneto regions, on the contribution of NO 2 , PM 2.5 , PM 10 , O 3 and SO 2 to the incidence, mortality, and fatality rates of COVID-19, both short- and long-term exposure for 8 years (January 2013–May 2020). The most striking result was the finding of the significant role of exposure to SO 2 in COVID-19 pandemic via inducing systemic and respiratory inflammation.…”
Section: Recent Studies By Continents and Countriesmentioning
confidence: 99%
“…had already been observed in comparison with other countries during this time period (the so-called second wave; Bontempi, 2021). A modification of the relationships between atmospheric parameters and the COVID-19 diffusion had been already observed earlier in Italy and it was due to the lockdown during the spring season ( Benedetti et al, 2020 ; Ho et al, 2021 ). Also, on a global scale the public health interventions are considered to induce a major impact on the prevention of COVID-19 diffusion in comparison with seasonal factors ( Jüni et al, 2020 ; Paraskevis et al, 2021 ).…”
Section: Discussionmentioning
confidence: 64%
“…the first month ( Pivato et al, 2021 ; Pirouz et al, 2020 ; Collivignarelli et al, 2021 ; Haghshenas et al, 2020 ; Bontempi, 2020 ; Passerini et al, 2020 ; Ye et al, 2021 ; Sfîcă et al, 2020 ; Khursheed et al, 2021 ; Coker et al, 2020 ; Bianconi et al, 2020 ; Accarino et al, 2021 ; Perone, 2021 ; Filippini et al, 2021 ; Kotsiou et al, 2021 ), or up to April 2020 ( Coccia, 2020 ; Delnevo et al, 2020 ; Fazzini et al, 2020 ; Filippini et al, 2020 ; Fattorini and Regoli, 2020 ; Zoran et al, 2020 ; De Angelis et al, 2021 ; Benedetti et al, 2020 ; Agnoletti et al, 2020 ). Only a few works have considered a wider time span, up to the end of spring ( Ho et al, 2021 ; Pansini and Fornacca, 2021 ; Lolli et al, 2020 ; Cascetta et al, 2021 ). The paper by Fiasca et al (2020) has studied the effect of air pollution until the end of November.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations